Bacterial meningitis caused by penicillin-resistant Neisseria lactamica - Papapetropoulou, Maria; Tzanakaki, Georgina; Papapetropoulos, Spiridon; Guevara-Salcedo, Alexandra; Leontsini, Fani; Kremastinou, Jenny; Karpathios, Themistoklis (Journal of Pediatric Infectious Diseases, 2008)
A case of a 5-year-old child with signs and symptoms of bacterial meningitis was admitted to the “Iatrikon Athinon” Medical Center, Athens, Greece. The isolated strain was identified as Neisseria lactamica. Susceptibility to penicillin, cefotaxime, ceftriaxone, tetracycline, sulfonamides, rifampicin, ciprofloxacin, erythromycin and chloramphenicol was determined twice by E-test. The isolate was resistant to penicillin (8 μg/mL) and erythromycin (64 μg/mL). Since antibiotic susceptibility testing revealed that the isolate was resistant to penicillin, the patient was successfully treated with ceftriaxone. This is a first report of a meningitis case due to penicillin-resistant N. lactamica in Greece.
Keywords: Neisseria lactamica; meningitis; penicillin; resistance